Comparison of the Efficacy of TNO and Titmus Fly in Myopic Anisometropes - Ayesha Kiran, Faisal Rashid, Muhammad Siddique, Maryam Jabbar, Muhammad Hamza Shahid, Sehrish Qayyum Khokhar, Mashal Niazi, Warda Aftab, Kousar Naseem (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The aim of this study is to evaluate the stereo acuity in anisometropic myopes and to compare efficacy of TNO and Titmus fly test. Methodology: The cross sectional study design was carried out from September 2021 to May 2022 at eye departments of different teaching hospitals of Punjab. A total study sample of 150 subjects age range between 11-33 years of both gender (male and female) having myopic anisometropia (with moderate and severe degree of anisometopia) were included in this study. All other types of refractive error except myopic anisometropes, all ocular pathologies and systemic pathologies were excluded from the study. After taking informed consent from the individual’s subject to undergo routine ophthalmological examinations, including slit lamp examination of the inner and posterior chamber of the eye and best corrected visual acuity of both eyes (BCVA). Steroacuity test TNO and Titmus were performed to evaluate the stereopsis of myopic anisometropes. Data analysis was done by SPSS version 20. Independent sample t test was used for statistically analysis. Results: Results showed that stereopsis gets reduced by myopic anisometropia. As the level of anisometropia increase from 1D and above, the stereopsis deteriorates in case of myopic anisometropia Conclusion: TNO is considered more reliable as compared to Titmus fly test as the level of difficulty is more in TNO and is independent of monocular clues.